Experimental study of a post-tensioned precast concrete beam-column joint with energy dissipaters and partially-precast slabs. (15th June 2023) - Qing, Yuan; Liu, Ye; Wang, Chun-Lin; Du, Dongsheng; Meng, Shaoping
Highlights: Evaluating the seismic performances of a novel beam-column joint named PPED-PPS. Discussing the seismic performance of the PPC-PPS specimens under a second loading. Verifying the feasibility of two post-loading repair methods for the PPC-PPS. Investigating the influences of the locations of the energy dissipaters on the responses of the PPC-PPS. Abstract: A post-tensioned precast concrete beam-column joint (PPED-PPS) with energy dissipaters and partially precast slabs was investigated in this paper; this joint was mainly composed of a precast column, a partially precast beam, four partially precast slabs, and energy dissipaters. The precast column and partially precast beam were assembled together by using post-tensioned tendons. Two batches of PPED-PPS specimens were designed and tested to investigate the seismic performance of the PPED-PPS in the following cases: failure of energy dissipaters, repeated loading and post-earthquake repairs. The experimental results illustrated that the PPED-PPS exhibited significant reductions in energy dissipation capacity and bearing capacity at a larger drift ratio after repeated loading and failure of the energy dissipaters. The partially precast slabs showed a series of interconnected cracks at larger displacement, extensively reducing the energy dissipation capacity and bearing capacity of the PPED-PPS specimen. By recasting the damaged slabs and replacing the energy dissipaters with new ones, an effective post-earthquake repair method for the PPED-PPS was implemented. Notably, the post-earthquake repair method did not increase the elastic deformation demands of post-tensioned tendons in the PPED-PPS.